GLOBAL BANKING CRISES: CAUSES, FACTORS AND IMPLICATIONS - Sh. U. Niyazbekova; S. T. Kosmagambetova (Финансы: теория и практика, 2017)
Modern banking crisis in Kazakhstan’s economy is part of the global financial crisis. Liquidity problems which have emerged in second-tier Kazakh banks are mostly caused by changes in the situation on global financial markets and reduced availability of free financial resources. However, the ongoing national banking crisis has its roots not only in the substantial involvement of Kazakhstan’s banking system in global financial markets but also in severe structural deformations which it has undergone over the past few years. The work is the result of research conducted by the authors in 2009-2013 on the basis of practical materials of domestic and foreign organizations. The paper describes an efficient method which has been successfully tested in practice to exit from or prevent the global banking crisis; it also suggests some efficient management solutions. Clear and transparent evaluations and projections set out in the paper may be used by large financial institutions, analysts,commercial banks.Some elements of the proposed technique maybe applied to analyse complexprojects,etc.